语言的妓女与嫖客 ：以华语语系探讨冼文光短篇小说集《柔佛海峡》= A sinophone study of Xian Wenguang collection of short stories Rou Fo Hai Xia (The Straits of Johor) - Ang, Jin Yong (2016)
华语是一种媒介，即可与中国保持紧密的关系，同时也可以被所在之地与所接触的不同文化而改变。近十年开始有愈来愈多的学者开始投入华语语系的研究，试图以“华语”作为一种“统一”的媒介，研究世界各地不同“种类”的华语群体与文学。然而，本文在进行调查的时候发现，许多学者着重于研究华语与方言群体的互动，却极少提及华语与其他不同语言（比如马来语、英语）的互动。因此，本文借用冼文光的小说集《柔佛海峡》，研究文本中体现的不同语言现象，试图验证华语并不是与中国有剪不断的关系，而是会进行改变与创新。语言即可是妓女，无法摆脱一种被“欺凌”的命运，但也同时可以是嫖客，与不同的“妓女”（语言）有“交汇”的现象。而当地的华人认同也会随着语言的改变产生“杂糅”的现象。Chinese Language is a medium in which Chinese people can maintain a form of connection with China, or interact with different cultures and evolve. There has been a trend in Sinophone studies, where researchers use Chinese as a “unifying language” to study the many different Chinese speaking communities over the world. However, this research shows that there is a lack of study into the interactions involving Chinese and other languages (For example, Malay or Indian). This paper hopes to provide some insight into this matter through the study of Xian Wenguang’s short story collection Rou Fo Hai Xia (The Straits of Johor). Language can be a “prostitute”, in the sense that it is unable to escape a certain “abusive” fate (which in the Chinese language case, is its relationship with China), but it can also be a client that “chooses” its “prostitute” (language) and interacts with them. The resulting sense of identity of the Chinese people is one of hybridity.